Characterization of Multiple-Antimicrobial-Resistant Escherichia coli Isolates from Diseased Chickens and Swine in China - Yang, Hanchun (American Society for Microbiology, 2004)
Escherichia coli isolates from diseased piglets (n = 89) and chickens (n = 71) in China were characterized for O serogroups, virulence genes, antimicrobial susceptibility, class 1 integrons, and mechanisms of fluoroquinolone resistance. O78 was the most common serogroup identified (63%) among the chicken E. coli isolates. Most isolates were PCR positive for the increased serum survival gene (iss; 97%) and the temperature-sensitive hemagglutinin gene (tsh; 93%). The O serogroups of swine E. coli were not those typically associated with pathogenic strains, nor did they posses common characteristic virulence factors. Twenty-three serogroups were identified among the swine isolates; however, 38% were O nontypeable. Overall, isolates displayed resistance to nalidixic acid (100%), tetracycline (98%), sulfamethoxazole (84%), ampicillin (79%), streptomycin (77%), and trimethoprim-sulfamethoxazole (76%). Among the fluoroquinolones, resistance ranged between 64% to levofloxacin, 79% to ciprofloxacin, and 95% to difloxacin. DNA sequencing of gyrA, gyrB, parC, and parE quinolone resistance-determining regions of 39 nalidixic acid-resistant E. coli isolates revealed that a single gyrA mutation was found in all of the isolates; mutations in parC together with double gyrA mutations conferred high-level resistance to fluoroquinolones (ciprofloxacin MIC, ≥8 μg/ml). Class 1 integrons were identified in 17 (19%) isolates from swine and 42 (47%) from chickens. The majority of integrons possessed genes conferring resistance to streptomycin and trimethoprim. These findings suggest that multiple-antimicrobial-resistant E. coli isolates, including fluoroquinolone-resistant variants, are commonly present among diseased swine and chickens in China, and they also suggest the need for the introduction of surveillance programs in China to monitor antimicrobial resistance in pathogenic bacteria that can be potentially transmitted to humans from food animals.